The GM2 glycan serves as a functional coreceptor for serotype 1 reovirus. - Kerstin Reiss; Jennifer E Stencel; Yan Liu; Bärbel S Blaum; Dirk M Reiter; Ten Feizi; Terence S Dermody; Thilo Stehle (PLoS Pathogens, 2012)
Viral attachment to target cells is the first step in infection and also serves as a determinant of tropism. Like many viruses, mammalian reoviruses bind with low affinity to cell-surface carbohydrate receptors to initiate the infectious process. Reoviruses disseminate with serotype-specific tropism in the host, which may be explained by differential glycan utilization. Although α2,3-linked sialylated oligosaccharides serve as carbohydrate receptors for type 3 reoviruses, neither a specific glycan bound by any reovirus serotype nor the function of glycan binding in type 1 reovirus infection was known. We have identified the oligosaccharide portion of ganglioside GM2 (the GM2 glycan) as a receptor for the attachment protein σ1 of reovirus strain type 1 Lang (T1L) using glycan array screening. The interaction of T1L σ1 with GM2 in solution was confirmed using NMR spectroscopy. We established that GM2 glycan engagement is required for optimal infection of mouse embryonic fibroblasts (MEFs) by T1L. Preincubation with GM2 specifically inhibited type 1 but not type 3 reovirus infection of MEFs. To provide a structural basis for these observations, we defined the mode of receptor recognition by determining the crystal structure of T1L σ1 in complex with the GM2 glycan. GM2 binds in a shallow groove in the globular head domain of T1L σ1. Both terminal sugar moieties of the GM2 glycan, N-acetylneuraminic acid and N-acetylgalactosamine, form contacts with the protein, providing an explanation for the observed specificity for GM2. Viruses with mutations in the glycan-binding domain display diminished hemagglutination capacity, a property dependent on glycan binding, and reduced capacity to infect MEFs. Our results define a novel mode of virus-glycan engagement and provide a mechanistic explanation for the serotype-dependent differences in glycan utilization by reovirus.